Peripapillary arterial circle of zinn-haller: location and spatial relationships with myopia - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (PLoS ONE, 2013)
To measure histomorphometrically the location of the peripapillary arterial circle of Zinn-Haller (ZHAC) and assess its associations with axial length.Using a light microscope, we measured the distance from the ZHAC to the peripapillary ring (optic disc border), the merging point of the dura mater with the posterior sclera ("dura-sclera point"), and the inner scleral surface. In the parapapillary region, we differentiated between beta zone (presence of Bruch's membrane, absence of retinal pigment epithelium) and gamma zone (absence of Bruch's membrane). The peripapillary scleral flange as roof of the orbital cerebrospinal fluid space was the connection between the end of the lamina cribrosa and the posterior full-thickness sclera starting at the dura-sclera point.The study included 101 human globes (101 patients) with a mean axial length of 26.7±3.7 mm (range: 20.0-39.0 mm). The distance between the ZHAC and the peripapillary ring increased significantly with longer axial length (P<0.001; correlation coefficient r = 0.49), longer parapapillary gamma zone (P<0.001;r = 0.85), longer (P<0.001;r = 0.73) and thinner (P<0.001;r = -0.45) peripapillary scleral flange, and thinner sclera posterior to the equator (P<0.001). ZHAC distance to the peripapillary ring was not significantly associated with length of parapapillary beta zone (P = 0.33). Including only non-highly myopic eyes (axial length <26.5 mm), the ZHAC distance to the disc border was not related with axial length (P = 0.84). In non-highly myopic eyes, the ZHAC was located close to the dura-sclera point. With increasing axial length and decreasing thickness of the peripapillary scleral flange, the ZHAC was located closer to the inner scleral surface.The distance between the ZHAC and the optic disc border is markedly enlarged in highly myopic eyes. Since the ZHAC is the main arterial source for the lamina cribrosa blood supply, the finding may be of interest for the pathogenesis of the increased glaucoma susceptibility in highly myopic eyes.
EVALuna2:21141